Modifiable and non-modifiable epidemiological risk factors for acne, acne severity and acne scarring among Malaysian Chinese: a cross-sectional study - Yee-How Say; Anna Hwee Sing Heng; Kavita Reginald; Yi Ru Wong; Keng Foo Teh; Smyrna Moti Rawanan Shah; Yang Yie Sio; Yu Ting Ng; Sri Anusha Matta; Sze Lei Pang; Fook Tim Chew (BMC, 2021)
Abstract Background Acne vulgaris, a highly prevalent multifactorial inflammatory skin disease, can be categorised into different severity and scarring grades based on the type, number, and severity of lesions. While many epidemiology studies have investigated the risk factors for acne presentation, fewer studies have specifically studied the risk factors for acne severity and scarring. Therefore, this study investigated the prevalence of acne, acne severity and scarring grades, and their associated non-modifiable and modifiable epidemiological risk factors among Malaysian Chinese. Methods A total of 1840 subjects (1117 cases/723 controls) completed an investigator-administered questionnaire as part of a cross-sectional study, which include socio-demographics, familial history, lifestyle factors, dietary habits, and acne history. Acne cases were further evaluated for their severity (n = 1051) and scarring (n = 1052) grades by a trained personnel. Results Majority of the acne cases (up to 69%) had mild acne or Grade 1/2 scarring, while 21.6% had moderate/severe acne and 5.5% had Grade 3/4 scarring. Males had significantly higher risk of presenting with higher grades of acne scarring. Those who had acne, regardless of severity and scarring grades, had strong positive familial history (either in parents and/or sibling). Frequent consumption (most or all days) of foods that are commonly consumed during breakfast (butter, probiotic drinks, cereals and milk) decreased the risk for acne presentation and higher acne scarring, while periodic consumption (once/twice per week) of nuts and burgers/fast food decreased the risk for higher acne severity. Alcohol drinking was significantly associated with increased risk for acne presentation, while paternal, parental and household smoking were associated with reduced risk of more severe acne. Conclusions In conclusion, positive familial history is a strong predisposing factor in influencing acne presentation, severity and scarring. Frequent consumption of foods that are commonly consumed during breakfast is protective against acne presentation.